The Palgrave Handbook of Methodological Individualism: Volume I - Bulle, Nathalie; Di Iorio, Francesco (Palgrave Macmillan, 2023)
Part I. The Founding Principles of MI -- 1. The Scottish Enlightenment and MI; Jeremy Shearmur -- 2. Weber /MI and sociological explanation; Wolfgang Schluchter -- 3. MI/ interpretative sociology; Stephen Turner -- 4. MI and the Austrian School of Economics; Peter Boettke -- 5. Actuality of the Weberian paradigm /MI; Thomas Schwinn -- 6. Holism and Individualism; Raymond Boudon -- Part II. MI and the Rationality Principle -- 7. IM, Rationality and Sociological Thought; Hartmut Esser -- 8. MI/Beliefs/rationality; Ian Jarvie -- 9. MI and Psychology (Emotions/Cognitive science); Paul Dumouchel -- 10. Cognitive Economy/Decisional Processes/Nudge Theory/MI; Riccardo Viale -- 11. Reasoning/beliefs/MI; Gérald Bronner -- 12. Axiological Rationality/MI; Sylvie Mesure -- Part III. MI and the Micro-Macro Link -- 13. MI/Micro–Macro Relationship in Social Science; Gustav Ramström -- 14. MI, Interpretivism and Unintended Consequences; Key Yoshida -- 15. MI/social structures; Pierre Demeulenaere -- 16. MI/micro-macro/ontology; Robert Sugden -- 17. MI/Complexity; Jean Petitot -- 18. MI/Stratification; Mohamed Cherkaoui -- Part IV. MI and Some Major Traditions of Social Science Research -- 19. MI/Marx; Jon Elster -- 21. MI/Durkheim; Massimo Borlandi -- 22. MI/ Weber/ Parsons/Schutz; Nasu Hisashi -- 23. MI/Hermeneutics/interpretative sociology; Enzo Di Nuoscio -- 24. Evolutionary Approach/Behavioral Sciences/Non-Atomistic MI; Herbert Gintis -- 25. Analytical Sociology/MI; José Antonio Noguera Ferrer.